PENGENTASAN BUTA AKSARA DAN PENGEMBANGAN PENDIDIKAN NON FORMAL DI DESA TERAK - Hikmawati, Agci; Apriani, Fitri; Arafatun, Sasih Karnita (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTTerak Village, located in Simpang Katis District, Central Bangka Regency, has significant natural potential, including waterfall tourist attractions and hilly areas, but faces serious challenges in the field of education. Based on available data, there are 13 village residents who are still illiterate and the school dropout rate is high, caused by internal factors such as low interest in learning, economic problems, and limited educational accessibility. The aim of this service is to overcome this problem through community empowerment in eradicating illiteracy and developing non-formal education in Terak Village. The methods used in this service include holding inspirational talk shows to strengthen educational motivation, as well as literacy training and non-formal education for children and the local community. It is hoped that through this activity, village communities, especially children, can gain a better understanding of the importance of education and can continue their education through the Community Learning Activity Center (PKBM). The expected results of this service are increased educational participation and a reduction in illiteracy and school dropout rates in Terak Village.Keywords: community empowerment, illiteracy, non-formal education, educational motivation, Terak VillageABSTRAKDesa Terak terletak di Kecamatan Simpang Katis, Kabupaten Bangka Tengah, memiliki potensi alam yang signifikan, termasuk objek wisata air terjun dan kawasan perbukitan. Namun, dalam bidang pendidikan, terdapat masyarakat yang masih buta aksara yang disebabkan oleh faktor-faktor internal seperti rendahnya minat belajar dan masalah ekonomi pada umumnya. Tujuan dari pengabdian ini adalah untuk mengatasi masalah tersebut melalui pemberdayaan masyarakat dalam mengentaskan buta aksara dan mengembangkan pendidikan non-formal di Desa Terak. Metode yang digunakan dalam pengabdian ini meliputi penyelenggaraan talk show inspiratif untuk penguatan motivasi pendidikan, serta pelatihan buta aksara dan pendidikan non-formal bagi masyarakat setempat. Diharapkan melalui kegiatan ini, masyarakat desa, khususnya anak-anak, dapat memperoleh pemahaman yang lebih baik tentang pentingnya pendidikan dan memberantas buta aksara. Hasil yang diharapkan dari pengabdian ini adalah peningkatan partisipasi pendidikan dan penurunan angka buta aksara di Desa Terak. Kata Kunci: pemberdayaan masyarakat, buta aksara, pendidikan non-formal, motivasi pendidikan, Desa Terak